Implementation of Character Education in Building Attitude Tolerance Students Through Social Studies Learning in Class V SD Inpres 1 Kayumalue Taxi - Mila Tamrin; Lukman; Misnah (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The purpose of study This that is For know the implementation process education Characters in Class V of SD Inpres 1 Kayumalue Pajeko , which is related with attitude tolerance participant the students who are taught through social studies learning , as well as factors supporters and inhibitors in build attitude tolerance participant educate . Research This done Because see problems that occur among children namely in conditions and circumstances environment participant Educate today , who behaves not enough value existence difference with other friends so the occurrence case bullying and also behaving not enough polite towards someone more old . Research This is study Qualitative through approach descriptive , with technique collection the data through method Observation , Interviews , and Documentation . From the research that has been conducted by the author , based on results observation in class V SD Inpres 1 Kayumalue Taxi obtained presentation accuracy of data in the field related to the “ Implementation ” process education character in build attitude tolerance participant educate through "social studies learning " reached (91.02%) including in Good category . Also supported by the results interview together Head Schools , Social Studies Teachers and Participants educate class V as informants who have give the information needed . The conclusion of research This is implementation education character through related social studies learning attitude tolerance , has taught by the social studies teacher in grade V with Good in KBM and always try to build participant educate be “ tolerant ” which means own attitude each other appreciate and respect others. Through social studies learning with method habituation , participants educate can Study about mark character build attitude tolerance for oneself Alone as well as practice it in a way direct in activity daily good in the environment school or public compound . With thus , the thing This will give impact positive for life . Behave tolerance will minimize the occurrence a conflict , disputes , discrimination , even fight so that everyone can​ doing activities with good , safe , comfortable , peaceful , and obeys the rules as well as life harmonious when side by side with other people with background different background .​